Development of Dynamic Local Work Load Measurement Method Using Electromyography (EMG) (an experimental measurement with drilling activities) - Lenny Saulia; Sam Herodian; I Dewa Made Subrata (Jurnal Keteknikan Pertanian, 2002)
This paper presents a scheme to build a system of musculosceletal maesurement using Electromyography and for measuring physical dynamic workload of local muscles, i.e., drilling activities. Electro-myography (EMG) can be signal of muscle contractions and provides continous record as the analog signal. The result of this dynamic local workload measurement show a nonlinear relationship between peak level power spectra of EMG signal and torque. the work load for drilling 0.8 mm to 5 mm plate activities ranges between 0,1513 to 1, 6979 Joule.